RESPONS PERTUMBUHAN DAN PRODUKSI PADI HIBRIDA TERHADAP APLIKASI PUPUK ORGANIK CAIR LIDAH BUAYA DAN PUPUK ANORGANIK P - wandansari, niken rani; Swandaru, Hendra; Cahya, Utik Tri Wulan (Universitas Tribhuwana Tunggadewi, 2024)
This research aimed to observe the growth and production response of the Inpari 32 hybrid rice variety to the application of aloe vera liquid organic fertilizer and inorganic P fertilizer compared to the absence of the combination of these two fertilizers. The research method used was comparative, comparing rice field plots treated with a combination of inorganic P fertilizer (Phonsgreen) at a dose of 150 kg/ha and aloe vera liquid organic fertilizer (P1) at a dose of 6 liters/ha with rice field plots without the combination of the two fertilizers (P0). Parameters observed included plant height, number of tillers, number of productive tillers, panicle length, number of grains per panicle, grain weight per clump, and weight of 1000 grains. The results showed that aloe vera liquid organic fertilizer and inorganic P fertilizer could increase milled dry grain production by up to 29.9%.